Overproduction of reactive oxygen species and activation of MAPKs are involved in apoptosis induced by PM2.5 in rat cardiac H9c2 cells. Issue 4 (15th October 2015) - Cao, Jing; Qin, Gang; Shi, Ruizan; Bai, Feng; Yang, Guangzhao; Zhang, Mingsheng; Lv, Jiyuan
Abstract: Epidemiological studies show a positive correlation between the air levels of fine particulate matter (PM2.5 ) and cardiovascular disorders, but how PM2.5 affects cardiomyocytes has not been studied in great deal. The aim of the present study was to obtain an insight into the links among intracellular levels of reactive oxygen species (ROS), apoptosis and mitogen‐activated protein kinases (MAPKs) in rat cardiac H9c2 cells exposed to PM2.5 . H9c2 cells were incubated with PM2.5 at 100–800 µg ml –1 to evaluate the effects of PM2.5 on cell viability, cell apoptosis, intracellular levels of ROS and expression of apoptosis‐related proteins as well as activation of MAPKs. PM2.5 decreased cell viability, increased the cell apoptosis rate and intracellular ROS production in a concentration‐dependent manner. PM2.5 decreased the Bcl‐2/Bax ratio and increased cleaved caspase‐3 levels. A Western blots study showed up‐regulation of phosphorylated MAPKs including extracellular signal‐regulated protein kinases (ERKs), c‐Jun NH2 ‐terminal kinases (JNKs) and p38 MAPK in the PM2.5 ‐treated cells. The p38 MAPK inhibitor SB239063 attenuated whereas the ERKs inhibitor PD98059 augmented the effects of PM2.5 on apoptosis and the expression of related proteins. In conclusion, PM2.5 decreases cell viability and increases apoptosis by enhancing intracellular ROS production and activating the MAPKs signaling pathway in H9c2 cells. The MAPKs signaling pathway could be a new promising target for clinical therapeutic strategies against PM2.5 ‐induced cardiac injury. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We present novel findings on the regulatory mechanisms of PM2.5 ‐induced myocardiocyte apoptosis. PM2.5 ‐induced apoptosis was associated with enhanced intracellular ROS production and mediated, at least partially, by a caspase‐3‐dependent, mitochondria/Bcl‐2 death pathway via the MAPKs signaling pathway in H9c2 cells. Our findings shed light on the stress signaling pathway involved in PM2.5 ‐induced apoptotic effects in H9c2 cells. The MAPKs signaling pathway could be a new promising target for clinical therapeutic strategies against PM2.5 ‐induced cardiac injury.